A case at crossroads—urological presentation, cardiac complication and haematological diagnosis: should imaging be pursued prior to orchidectomy at all costs?. Issue 5 (14th May 2021) - Yasen, Zaid; Kazzazi, Fawz; Ioannides, Kyriacos; Velmurugan, Shanti; Zegocki, Kris; Li, Chi
ABSTRACT: This case report explores the interesting case of a 71-year-old gentleman who presented with a testicular lump following trauma. Ultrasound imaging of the testicle demonstrated malignancy and subsequently orchidectomy was listed. Due to a scheduling difficulty, this was prioritized ahead of his whole-body computed tomography scan. Intraoperatively, he developed electrocardiogram changes suggestive of a non-ST elevated myocardial infarction. Post-operative imaging demonstrated a diffuse large B-cell lymphoma encroaching the heart and greater vessels. This case report highlights the importance of preoperative imaging, even where it may prove challenging. We assess the adequacy of current guidelines within the UK on imaging for new testicular malignancies.